Analisis Hypothetical Learning Trajectory (HLT) Pada Mata Kuliah Pembelajaran Matematika SD Mahasiswa PGSD - Benu, Rince S. M; Nifu, Adam Bol; W. Ndolu, Sumardi (STKIP Andi Matappa Pangkep, 2024)
One of the competencies that students must achieve in the Elementary Mathematics Learning course is the ability to design mathematics learning activities, but some students experience difficulties in designing mathematics learning activities. The forms of difficulties faced include the formulation of indicators and the formulation of learning objectives in accordance with basic competencies. The purpose of the research is to develop the ability of PGSD students to develop HLT designs on mathematics materials in elementary schools. The method used in this study is descriptive qualitative and the data obtained is in the form of HLT design portfolios. The results of the study show that students can design HLT in a good category covering 3 aspects, goal math, student thinking & teacher support. The design of the Hypothetical learning trajectory (HLT) in mathematics learning in elementary schools can be used by students/teachers as a guideline to predict and prepare a learning flow design that is in accordance with the students' thinking stages and is expected to improve student learning outcomes.